2008
DOI: 10.1161/hypertensionaha.107.109173
|View full text |Cite
|
Sign up to set email alerts
|

Renal Regional Proteomes in Young Dahl Salt-Sensitive Rats

Abstract: Abstract-We performed an extensive proteomic analysis of the Dahl model of salt-sensitive hypertension. The consomic SS-13 BN rat, genetically similar to the Dahl salt-sensitive rat, while exhibiting a significant amelioration of salt-induced hypertension, was used as a control. Proteomic analysis, using differential in-gel electrophoresis and mass spectrometry techniques, was performed in the renal cortex and the renal medulla of 6-week-old SS and SS-13 BN rats before significant differences in blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 28 publications
6
72
0
Order By: Relevance
“…Yet another possibility is that excess glucocorticoids might upregulate local expression of angiotensinogen in the renal medulla, reminiscent of the observations in mice overexpressing 11␤-HSD1 (28,31). We recently found that angiotensinogen expression in the renal medulla was upregulated by a high-salt diet in SS rats but downregulated in SS-13 BN rats (44).…”
Section: Discussionmentioning
confidence: 91%
“…Yet another possibility is that excess glucocorticoids might upregulate local expression of angiotensinogen in the renal medulla, reminiscent of the observations in mice overexpressing 11␤-HSD1 (28,31). We recently found that angiotensinogen expression in the renal medulla was upregulated by a high-salt diet in SS rats but downregulated in SS-13 BN rats (44).…”
Section: Discussionmentioning
confidence: 91%
“…HK-2, a human kidney epithelial cell line, was obtained from and cultured as suggested by American Type Culture Collection (48,49). Cells at ϳ40% confluence were treated with recombinant human transforming growth factor (TGF)-␤1 (3 ng/ml, R&D Systems) or the vehicle control in DMEM for the indicated time period.…”
Section: Experimental Animal Protocolmentioning
confidence: 99%
“…The relative abundance of several proteins was analyzed using Western blotting or immunohistochemistry (IHC) as we described previously (3,16,21,27,48,53). Antibodies were from Sigma-Aldrich, Abcam, Novus Biologicals, Bioworld, or Jackson ImmunoResearch.…”
Section: Experimental Animal Protocolmentioning
confidence: 99%
“…This is illustrated by our previous work on molecular networks underlying Dahl salt-sensitive hypertension, which has led to several novel discoveries regarding the overall network (9) and specific components of the network (11,20,22,23).…”
mentioning
confidence: 94%